Fibrin and poly(lactic-co-glycolic acid) hybrid scaffold promotes early chondrogenesis of articular chondrocytes: an in vitro study - Sha'ban, Munirah; Hee Kim, Soon; BH Idrus, Ruszymah; Khang, Gilson (BioMed Central Ltd., 2008)
Background: Synthetic- and naturally derived- biodegradable polymers have been widely used to construct scaffolds for cartilage tissue engineering. Poly(lactic-co-glycolic acid) (PLGA) are bioresorbable and biocompatible, rendering them as a promising tool or clinical application. To minimize cells lost during the seeding procedure, we used the natural polymer fibrin to immobilize cells and to provide homogenous cells distribution in PLGA scaffolds. We evaluated in vitro chondrogenesis of rabbit articular chondrocytes in PLGA scaffolds using fibrin as cell transplantation matrix. Methods: PLGA scaffolds were soaked in chondrocytes-fibrin suspension (1 × 106cells/scaffold) and polymerized by dropping thrombin-calcium chloride (CaCl2) solution. PLGA-seeded chondrocytes was used as control. All constructs were cultured for a maximum of 21 days. Cell proliferation activity was measured at 1, 3, 7, 14 and 21 days in vitro using 3-(4,5-dimethylthiazole-2-yl)-2-, 5-diphenyltetrazolium-bromide (MTT) assay. Morphological observation, histology, immunohistochemistry (IHC), gene expression and sulphated-glycosaminoglycan (sGAG) analyses were performed at each time point of 1, 2 and 3 weeks to elucidate in vitro cartilage development and deposition of cartilage-specific extracellular matrix (ECM). Results: Cell proliferation activity was gradually increased from day-1 until day-14 and declined by day-21. A significant cartilaginous tissue formation was detected as early as 2-week in fibrin/PLGA hybrid construct as confirmed by the presence of cartilage-isolated cells and lacunae embedded within basophilic ECM. Cartilage formation was remarkably evidenced after 3 weeks. Presence of cartilage-specific proteoglycan and glycosaminoglycan (GAG) in fibrin/PLGA hybrid constructs were confirmed by positive Safranin O and Alcian Blue staining. Collagen type II exhibited intense immunopositivity at the pericellular matrix. Chondrogenic properties were further demonstrated by the expression of genes encoded for cartilage-specific markers, collagen type II and aggrecan core protein. Interestingly, suppression of cartilage dedifferentiation marker; collagen type I was observed after 2 and 3 weeks of in vitro culture. The sulphatedglycosaminoglycan (sGAG) production in fibrin/PLGA was significantly higher than in PLGA. Conclusion: Fibrin/PLGA promotes early in vitro chondrogenesis of rabbit articular chondrocytes. This study suggests that fibrin/PLGA may serve as a potential cell delivery vehicle and a structural basis for in vitro tissue-engineered articular cartilage.